(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2020)
This study re-evaluates the claims of some scholars linking the fall of Melaka in 1511 with the atrocities and shortcomings of Sultan Mahmud Syah’s reign (1481-1528). In their writings, Sultan Mahmud Syah was described as a very cruel and absolute ruler. Among his major atrocities was his decision to mete out the death sentence on several individuals, especially on Bendahara Tun Muzahir and his family. This was allegedly done because of the king’s jealousy with regard to the Bendahara’s decision to marry his daughter Tun Fatimah to her cousin Tun Ali, without introducing Tun Fatimah to the king first. The ’murder’ is said to have left a devastating impact on Melaka’s political stability, which enabled the Portuguese to conquer Melaka in 1511. By reviewing the conflict between Sultan Mahmud Syah and Tun Muzahir and the fall of Melaka as described in the Sulalat-us-Salatin, Portuguese sources and secondary sources, this study attempts to reassess the truth behind the allegations. This study suggests that Sultan Mahmud Syah’s decision to punish the weak and corrupt Bendahara Tun Muzahir was a necessary act and a process of political cleansing that saved Melaka from greater damage. This study also shows that the fall of Melaka had no direct connection with the execution of Tun Muzahir. Instead,th is study explains that the fall of Melaka was largely due to foreign betrayal, which took advantage of the weakness of Tun Muzahir’s administration to conspire with the Portuguese to capture the city of Melaka in 1511. Keywords: Sultan Mahmud Syah, Bendahara Tun Muzahir, Melaka, Portuguese, Tun Fatimah, Sulalat-us-Salatin